KONDISI TEGAKAN TINGGAL DI KAW ASAN DUA PERUSAHAAN HUTAN DI RIAU - Sona Suhartana; Maman Mansyur Idris (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
Log skidding activities using tractors usually caused high residual stand damages. To reduce the residual stand damages, the factors influencing them must be identified. A study was carried out at two forest concessions in Riau in 1995. The aims of the study are : 1) to find the level of residual stand damages caused by felling ang skidding, 2) to identifY the factors influancing the residual stand damages and 3) to find the way of reducing residual stand damages.Data collected were the number of felled tress, trees with diameter 20 cm and up and damaged trees. The data was analysed by using the multiple regression.The results of the study show : 1) The average of residual stand damages caused by fellingis 11.5 %; 2) The average of residual stand damages caused by skidding is 15.4 %; and 3) The influence of the number of felled tress, stand density and the slope were highly significant to residual stand damages.Knowing the factors influencing the residual stand damages, ones should be easy to find the way of reducing that damages.Key words : felling, skidding, felled trees, residual stand damage